Digital rectal examination and its associated factors in the early detection of prostate cancer: a cross-sectional population-based study - Samara Carollyne Mafra Soares; Marianna de Camargo Cancela; Arn Migowski; Dyego Leandro Bezerra de Souza (BMC, 2019)
Abstract Background Digital rectal examination (DRE) is one of the most common strategies for prostate cancer early detection. However, the use for screening purposes has a controversial benefit and potential harms can occur due to false-positive results, overdiagnosis and overtreatment. The objective of this study is to calculate the prevalence and identify factors associated with the receipt of DRE in Brazilian men. Methods We selected men older than 40 from a nationwide population-based survey (13,625 individuals) excluding those with prostate cancer diagnosis. Information was extracted from the most recent database of the Brazilian National Health Survey (PNS 2013). Statistical analysis was carried out to calculate incidence rate ratios, with 95% confidence intervals and p values, through multivariate analysis with Poisson regression and robust variance. Results Men having private health insurance (63.3%; CI = 60.5-66.0) presented higher prevalence of DRE than those in the public health system (41.6%; CI = 39.8-43.4). The results show a positive association between DRE and men having private health insurance, aged 60-69, living with a spouse, never smokers, and living in urban areas. Among public health services users, this positive association was observed among men aged 70-79, living with a spouse, having bad/very bad health self-perception, abstainers, ex-smokers, with undergraduate studies, presenting four or more comorbidities, and residing in urban areas. Conclusions Prostate cancer screening with DRE is quite frequent in Brazil, specially among men with private health plans and better access to health services, healthier lifestyle and at more advanced ages, characteristics which increase the risk of overdiagnosis and overtreatment.